Polsko-rosyjskie porównania międzykulturowe w podręcznikach do nauki języka rosyjskiego na poziomie gimnazjalnym - Karolczuk, Marzanna (Studia Rossica Posnaniensia, 2017)
Comparing and contrasting cultural, lexical and grammatical aspects in the foreign language classroom has many advantages. These include the development of intercultural competence, cultural awareness and a new insight into the first language. Research shows that foreign language textbooks are basic teaching tools. Therefore, this article is an attempt to analyse Polish-Russian tasks and comparative content in Russian textbooks at the level of lower secondary school. Five textbook series for learning Russian, published between 1999 and 2009, are examined. These are В Москву, Времена, Кл@ссно!, Прогулка and Эхо. The findings show that these textbooks offer comparative reflective tasks and reconstructive ones.